Research on the Evolution of Operator’s SDP in Mobile Internet Era - Bin Dong; Wei Pan; Zheng Wang; Yanjie Zhao (Dianxin kexue)
With the rapid development of mobile smart phone and OTT applications，the traditional ecological environment of mobile value-added service based on operator’s SDP has been greatly impacted.It is important to enhance new capabilities of SDP.The SDP’s core value and years of experience in practice was summed up，and the challenge which SDP faced in the mobile internet era were analyzed.In addition，with the introduction of network capability open，new business support needs and new technologies such as cloud computing，some advices of the evolution and developement of operator’s SDP were proposed.